Mercenaries in the Democratic Republic of the Congo - González Durán, María Alejandra (2025)
The use of mercenaries in the Democratic Republic of Congo (DRC) has been a recurrent phenomenon throughout its history, linked to internal conflicts, foreign interests and the exploitation of natural resources. In this sense, this study analyzes three aspects of this problem. First, it analyzes the reasons why international actions to counteract mercenaries have not had the necessary effect, dividing them into formal and substantive reasons. Secondly, the enrollment of children and young people in armed groups is addressed as a problem, specifically analyzing two types of enrollment. Finally, transdisciplinarity and impunity in the territory are studied through environmental and geopolitical perspectives. The paper concludes that more effective international actions are needed, including the regulation of private security companies, the fight against corruption and the protection of the rights of children and youth affected by war.